Exploring Survey-Based Water, Sanitation, and Animal Associations With Enteric Pathogen Carriage: Comparing Results in a Cohort of Cases With Moderate-to-Severe Diarrhea to Those in Controls in the Vaccine Impact on Diarrhea in Africa (VIDA) Study, 2015–2018. (19th April 2023) - Berendes, David M; Omore, Richard; Prentice-Mott, Graeme; Fagerli, Kirsten; Kim, Sunkyung; Nasrin, Dilruba; Powell, Helen; Jahangir Hossain, M; Sow, Samba O; Doh, Sanogo; Jones, Joquina Chiquita M; Ochieng, John B; et al.
Abstract: Background: The magnitude of pediatric enteric pathogen exposures in low-income settings necessitates substantive water and sanitation interventions, including animal feces management. We assessed associations between pediatric enteric pathogen detection and survey-based water, sanitation, and animal characteristics within the Vaccine Impact on Diarrhea in Africa case-control study. Methods: In The Gambia, Kenya, and Mali, we assessed enteric pathogens in stool of children aged <5 years with moderate-to-severe diarrhea and their matched controls (diarrhea-free in prior 7 days) via the TaqMan Array Card and surveyed caregivers about household drinking water and sanitation conditions and animals living in the compound. Risk ratios (RRs) and 95% confidence intervals (CIs) were calculated using modified Poisson regression models, stratified for cases and controls and adjusted for age, sex, site, and demographics. Results: Bacterial (cases, 93%; controls, 72%), viral (63%, 56%), and protozoal (50%, 38%) pathogens were commonly detected (cycle threshold <35) in the 4840 cases and 6213 controls. In cases, unimproved sanitation (RR, 1.56; 95% CI, 1.12–2.17), as well as cows (RR, 1.61; 95% CI, 1.16–2.24) and sheep (RR, 1.48; 95% CI, 1.11–1.96) living in the compound, were associated with Shiga toxin–producing Escherichia coli . In controls, fowl (RR, 1.30; 95% CI, 1.15–1.47) were associated with Campylobacter spp. In controls, surface water sources were associated with Cryptosporidium spp., Shigella spp., heat-stable toxin-producing enterotoxigenic E. coli, and Giardia spp. Conclusions: Findings underscore the importance of enteric pathogen exposure risks from animals alongside more broadly recognized water and sanitation risk factors in children. Abstract : We assessed survey-based water, sanitation, and animal factors associated with enteric pathogens in cases of moderate to severe diarrhea and controls. Animals, cows and sheep (cases) and fowl (controls), were associated with bacterial carriage; surface water was associated with bacteria and protozoa in controls.